Методологічні засади оцінювання інвестиційних проектів в умовах невизначеності - Гойко, А. Ф.; Сорокіна, Л. В. (Ways to Improve Construction Efficiency, 2013)
Methodological approach to the evaluation of investments in economic activities in the context of macroeconomic instability and uncertainty about the trend of national economic development. The basis of the approach is the binomial option-pricing model.